THE IMPACT OF RECREATIONAL IN HUMAN HEALTH - Enver Tahiraj; Admira Koničanin; Afrim Shabani; Fikret Shatri; Bahri Gjinovci; Malësor Gjonbalaj (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Of Recreation knows no gender or age, knows no season or time of day. Health is a state of complete, physical, mental and social well-being and not merely absence of disease. The movement is an important feature of life. Therefore, the muscle activity of the best physiological way to stimulate the body's various systems